(untitled) (Eurasian Journal of Ecology, 2024)
ELEMENTAL COMPOSITION OF THE ASH OF POPLAR LEAVES AS AN INDICATOR OF TECHNOGENESIS ON THE EXAMPLE OF THE TERRITORY OF SOUTH KAZAKHSTAN One of the most important problems facing the community is the progressive pollution of the environment by technogenic factors. To obtain a general picture of pollution and the degree of impact on the environment, an integrated approach is required when studying the ecological state of the territory of Southern Kazakhstan. The article presents original data on the ecological and geochemical characteristics of the distribution of chemical elements in the ash of leaves of pyramidal poplar (Populus nigra f. pyramidalis), since this substrate accumulates pollutants from the environment. Analytical studies were carried out in the laboratory of Tomsk Polytechnic University using the INAA method (instrumental neutron activation analysis). Statistical parameters showed that Ca, Rb, Sr have a normal distribution, uneven distribution is typical for: As, Ag, Nd, Tb, Yb, Cr, Br, Sb, Cs, Ba, Sm, Eu, Lu, Ta, Au. The conducted cluster analysis showed 7 significant associations of chemical elements. In order to identify regional specifics, geochemical series were built relative to the clark of the noosphere, the relative average composition of living matter and literature data. The results of the analysis showed that the specific elements in the ashes of the pyramidal poplar leaves collected in the territory of South Kazakhstan are Na, Ca, As, Sr, Ag, Sb, Ba, Ta, U. Key words: elemental composition, South Kazakhstan, bioindicator, pyramidal poplar leaf ash (Populus nigra f. pyramidalis), instrumental neutron activation analysis.